2007
DOI: 10.1088/0964-1726/16/6/028
|View full text |Cite
|
Sign up to set email alerts
|

An improved analysis of the SSHI interface in piezoelectric energy harvesting

Abstract: This paper provides an analysis for the performance evaluation of a piezoelectric energy harvesting system using the synchronized switch harvesting on inductor (SSHI) electronic interface. In contrast with estimates based on a variety of approximations in the literature, an analytic expression of harvested power is derived explicitly and validated numerically for the SSHI system. It is shown that the electrical response using an ideal SSHI interface is similar to that using the standard interface in a strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
292
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(299 citation statements)
references
References 69 publications
7
292
0
Order By: Relevance
“…Now the basic principles of the nonlinear conversion enhancement exposed, this section proposes the direct application of this concept to energy harvesting, leading to the concept of Synchronized Switch Harvesting on Inductor Lefeuvre et al, 2006a;Shu, Lien and Wu, 2007;Liang and Liao, 2009;Qiu et al, 2009b). Considering the standard energy harvesting interface that consists in connecting the piezoelectric element to a smoothing capacitor C S and load R L (that represents the connected device) through a diode bridge rectifier (Figure 4(a)), the switching element may be placed in two ways: When using the standard interface, it can be demonstrated that the harvested energy under a constant vibration magnitude u M is given in steady state case by : …”
Section: Ssh Techniquesmentioning
confidence: 99%
“…Now the basic principles of the nonlinear conversion enhancement exposed, this section proposes the direct application of this concept to energy harvesting, leading to the concept of Synchronized Switch Harvesting on Inductor Lefeuvre et al, 2006a;Shu, Lien and Wu, 2007;Liang and Liao, 2009;Qiu et al, 2009b). Considering the standard energy harvesting interface that consists in connecting the piezoelectric element to a smoothing capacitor C S and load R L (that represents the connected device) through a diode bridge rectifier (Figure 4(a)), the switching element may be placed in two ways: When using the standard interface, it can be demonstrated that the harvested energy under a constant vibration magnitude u M is given in steady state case by : …”
Section: Ssh Techniquesmentioning
confidence: 99%
“…They have claimed that the harvested electrical power may be increased by as much as 900% over the standard technique. Then, Sue et al [29] detailed the analysis for the performance of a piezoelectric energy harvesting system using the synchronized switch harvesting on inductor (SSHI) electronic interface. It shows that the electrical response using an ideal SSHI interface is similar to that using the standard interface in a strongly coupled electromechanical system operated at short circuit resonance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, single crystals are difficult to obtain, and no industrial process has been achieved, compromising the design of low-cost microgenerators using such materials. In order to enhance the harvesting abilities, a nonlinear approach has been proposed that allows an artificial increase of the global electromechanical coupling coefficient Lefeuvre et al, 2006;Makihara, Onoda and Miyakawa, 2006;Qiu et al, 2009;Shu, Lien and Wu, 2007). This process consists of quickly inverting the piezoelectric voltage when the displacement or temperature reaches a maximum or a minimum value (or equivalently when the velocity cancels), as shown in Figure 4.…”
Section: Conversion Improvementmentioning
confidence: 99%